MEMS-based wide-bandwidth electromagnetic energy harvester with electroplated nickel structure. (5th October 2017) - Sun, Shi; Dai, Xuhan; Sun, Yunna; Xiang, Xiaojian; Ding, Guifu; Zhao, Xiaolin
Abstract: A novel nickel-based nonlinear electromagnetic energy harvester has been designed, fabricated, and characterized in this work. Electroplated nickel is very suitable for a stretching-based mechanism to broaden the bandwidth due to its good process and mechanical properties. A strong hardening nonlinearity is induced due to the large deformation of the thin nickel based guided-beam structure. Combining the merits of both the mechanical properties and guided-beam structure, the energy harvester shows good bandwidth performance. It is found that increasing the thickness of the central platform could guarantee nonlinearity. Static and dynamic models of the energy harvester are simulated and validated. Test results show that the energy harvester has good repeatability without any destruction under a large deformation condition. At the acceleration of 0.5 g, comparative large bandwidths of 129 and 59 Hz are obtained for displacement and RMS output voltage, respectively. Power output of 3.4 µ W and normalized power density of 125.92 µ W cm −3 g −2 are achieved with the load resistance of 38 Ω.